PENGARUH EKSTRAK DAUN SAGA PADA PROSES PENYEMBUHAN ULKUS TRAUMATIKUS MUKOSA MULUT TIKUS PUTIH JANTAN (Rattus Novegicus) (in vivo) - Ong Jonathan; Siti Chumaeroh; Moh Baehaqi; Oediani Santoso (Jurnal Medali, 2013)
Traumaticus ulcer or often called thrush is an issue that often comes up in society as it causes pain. People believe that the saga leaves can heal the ulcer. Previous research mentions saga leaves have anti-inflammatory substances.This research aims to determine the effect of Saga leaf (Abrus precatorius) against ulcerative traumatikus in vivo to Rattus Novegicus. This is experimental research which design randomized post test only control group, with Rattus Novegicus. In this research there were four group treatments. Data used to calculate the number of fibroblasts in 4 each visual field preparate. The research used statistical analysis Independent T test.The results of the average number of fibroblasts in each group were K3, K7, P3, P7 is 23.34, 18.83, 47.00, 23.83. Independent T Test obtained value of p <0.05 on day 3 but not on day 7. This means there was inhibition effect produced by extracts of saga leaves on day 3 but not on day 7.From the results, it can be concluded that the leaf extract Saga (Abrus precatorius) has an influence on ulcer healing traumatikus on Rattus Novegicus which have been shown number of fibroblasts.Â Key Words : Saga Leaf extract, traumatic ulcer